Representations of the city as a space of insecurity and crime: Lisbon, 1850-1910 - Vaz, M. J. (IX Congresso AISU: La citta globale – la condizione urbana come fenomeno pervasivo, 2019)
The relationship between crime and the city, the idea that the city favoured the practice of crime, was a recurring issue in the 19th century. In Portugal, this idea mainly concerned the city of Lisbon. Using diverse documentation, this communication analyses the representations of the city understood as an insecure and criminal space, as opposed to the idyllic constructions then made about life in the countryside and the narratives that define the city as a space of modernity and well-being.